Hubungan Toxic Parents dengan Kesehatan Mental Remaja di MTs Krueng Raya - Alfidanur Mulia; Urip Pratama; Ellyza fazlylawati (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Teenagers are in a developmental phase that is highly sensitive to various environmental influences, particularly those from their parents. Unhealthy parenting styles, also known as toxic parents, have a high potential to harm teenagers' psychological well-being. This study aims to determine the relationship between toxic parenting behavior and the mental health of teenagers in MTsS Krueng Raya. This research employed a quantitative method with a cross-sectional approach. The population consisted of 74 people, with a sample of 63 teenagers selected using a proportional random sampling technique. The instruments used were the Indonesian Version of the Poisonous Parenting Style Scale (IVPPSS) questionnaire to measure toxic parents and the Difficulties in Emotion Regulation Scale (DERS) to measure mental health. The data was analyzed using the Chi-Square test. The research results indicated a significant relationship between toxic parents and teenagers' mental health, with a ρ-value of 0.001 (p < 0.05). This study concludes that the higher the level of toxic parents, the lower the level of teenagers' mental health. Parents are expected to adopt supportive parenting styles, and schools are expected to provide counseling services to maintain students' mental health.